Negative plate, preparation method thereof and lithium battery

By adding metal oxides with an opal structure to the active layer of the negative electrode sheet of the lithium-ion battery, the problem of degradation of the rate performance of the lithium-ion battery when improving the energy density is solved, and the consideration of high energy density and high rate performance is achieved.

CN119419211AActive Publication Date: 2025-02-11BATTERO TECH CORP LTD

Patent Information

Application Number
CN202411550370.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-11
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

While improving the energy density, existing lithium-ion batteries are difficult to maintain high-rate performance, mainly due to the insufficient porosity of the negative electrode sheet and the electrolyte wetting ability, resulting in a decrease in the ion transfer rate.

Method used

The metal oxide with an inverse opal structure is added to the active layer of the negative electrode sheet, and the porosity and electrolyte wetting properties of the negative electrode sheet are improved by adjusting the hierarchical distribution and particle characteristics of the additives.

Benefits of technology

It improves the rate performance and energy density of the negative electrode sheet, reduces the internal resistance of the battery cell, ensures the transmission rate of lithium ions, and improves the power performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419211A_ABST
    Figure CN119419211A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses a negative plate, a preparation method thereof and a lithium battery. The negative plate comprises a current collector and an active layer arranged on the surface of the current collector; the active layer comprises a negative electrode active material, a conductive agent, an adhesive and an additive; the additive is a metal oxide with an inverse opal structure. The metal oxide with the inverse opal structure is added into the active layer of the negative electrode plate, and the metal oxide can endow the negative electrode plate with a special pore structure, so that the porosity of the negative electrode plate is improved, the wettability of an electrolyte to the negative electrode plate is improved, and the liquid retention capacity of the negative electrode plate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium batteries, and in particular to a negative electrode sheet and a preparation method thereof, and a lithium battery. Background Art

[0002] Lithium-ion secondary battery technology is developing rapidly and its application scope is becoming wider and wider. At present, the market has higher and higher performance requirements for lithium-ion batteries, requiring lithium-ion batteries to have high energy density and high rate performance. Conventional graphite and silicon negative electrode lithium-ion batteries, when increasing the coating amount of the pole piece and the compaction density of the material to improve the energy density of lithium-ion batteries, because conventional materials are solid and non-porous structures, this will cause the tortuosity of the pole piece to increase significantly, the electrolyte infiltration degree to decrease, and the ion transmission rate to decrease, which will cause the rate performance to decrease and the power performance of the battery to be lost. In order to achieve both high energy density and high rate performance of lithium-ion batteries, it is necessary to increase the specific surface area of ​​the negative electrode material used, the porosity of the negative electrode piece, optimize the microporous structure of the pole piece, and improve the energy density while ensuring the lithium ion transmission rate.

[0003] Currently, the main ways to increase the porosity of the negative electrode sheet and improve the wettability of the electrolyte are adding pore-forming agents, laser drilling, etc. Among them, the method of adding pore-forming agents has no lithium storage capacity, and the residue will increase the proportion of impurities and affect the performance and energy density of the lithium battery. The laser drilling method is costly and increases the drilling process.

[0004] In view of this, this application is hereby filed. Summary of the invention

[0005] The purpose of the present application is to provide a negative electrode sheet and a preparation method thereof and a lithium battery.

[0006] This application is implemented as follows:

[0007] In a first aspect, the present application provides a negative electrode sheet, comprising a current collector and an active layer disposed on a surface of the current collector;

[0008] The components of the active layer include negative electrode active materials, conductive agents, adhesives and additives;

[0009] The additive is a metal oxide having an inverse opal structure.

[0010] In an optional embodiment, the active layer is a multi-layer structure;

[0011] Along the direction away from the current collector, the additive content of each layer in the active layer of the multilayer structure gradually increases.

[0012] In an optional embodiment, the content of the additive in each layer of the multilayer structure of the active layer satisfies the following formula: The active layer closest to the current collector is the first layer, a1 is the percentage of the additive in the first layer to the entire active layer mass, a n is the percentage of the additive in the nth layer to the total active mass, n is the current layer number, n 总 is the total number of active layers, n 总 ≥2, p is the mass percentage of the additive in the entire active layer, 0.1%≤p≤50%;

[0013] When n 总 ≥2,0≤a1 <p / n 总 , a n Starting from the current collector side, it gradually increases to the outermost layer.

[0014] In an alternative embodiment, the metal oxide satisfies:

[0015] The D50 of the metal oxide is 1-40 μm; and / or the internal pore size of the metal oxide particles is 0.05-20 μm, and the internal pore volume accounts for 50-90% of the particle volume.

[0016] In an optional embodiment, the metal oxide is selected from at least one of titanium dioxide, tin dioxide and germanium dioxide.

[0017] In an optional embodiment, the active layer comprises, by mass percentage, 43-97.9% of negative electrode active material, 0.5-3% of conductive agent, 1-2.5% of binder and 0.1-50% of additive.

[0018] In an optional embodiment, the active layer further comprises 0.5 to 1.5% of a dispersant by mass percentage;

[0019] The dispersant is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium carboxyethyl cellulose.

[0020] In an optional embodiment, the invention further comprises at least one of the following features (1)-(4):

[0021] (1) the conductive agent is selected from at least one of carbon black, graphite flakes, carbon nanotubes and graphene;

[0022] (2) the adhesive is selected from at least one of styrene-butadiene rubber, sodium polyacrylate, sodium alginate and polyacrylonitrile;

[0023] (3) The negative electrode active material is at least one selected from graphite, hard carbon, soft carbon, lithium titanate and mesophase carbon microspheres;

[0024] (4) Active layers are provided on both opposite sides of the current collector.

[0025] In a second aspect, the present application provides a method for preparing a negative electrode sheet, which is used to prepare a negative electrode sheet as in any of the aforementioned embodiments, comprising coating a negative electrode slurry containing various components of an active layer on the surface of a current collector, followed by drying and cold pressing.

[0026] In a third aspect, the present application provides a lithium battery, comprising a negative electrode sheet as described in any of the aforementioned embodiments.

[0027] This application has the following beneficial effects:

[0028] The negative electrode sheet provided in the embodiment of the present application has a metal oxide with an inverse opal structure added to the active layer of the negative electrode sheet. The metal oxide can give the negative electrode sheet a special pore structure, increase the porosity of the negative electrode sheet, increase the wettability of the electrolyte to the negative electrode sheet, and increase the liquid retention of the negative electrode sheet. When a metal oxide with a lithium storage function is selected as an additive, the lithium storage capacity of the negative electrode will not be reduced. Therefore, by adding a metal oxide with an inverse opal structure to the negative electrode active layer, the rate performance of the negative electrode sheet can be increased, the internal resistance of the battery cell can be reduced, and the transmission rate of lithium ions can be guaranteed at the same time. This negative electrode sheet can improve the problem of reduced electrolyte infiltration and reduced ion transmission rate caused by increasing the coating amount of the electrode sheet and the compaction density of the material to increase the energy density of the lithium-ion battery, thereby causing a decrease in rate performance and loss of battery power performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The schematic diagram of the simulated structure of the active layer of the negative electrode sheet prepared in Example 2;

[0031] Figure 2 Schematic diagram of the simulated structure of the active layer of the negative electrode sheet prepared in Example 3.

[0032] Icons: 1-inverse opal porous layer; 2-graphite layer; 3-current collector; 4-inverse opal and graphite mixed porous layer. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0035] An embodiment of the present application provides a negative electrode sheet, comprising a current collector and an active layer arranged on the surface of the current collector;

[0036] The components of the active layer include negative electrode active materials, conductive agents, adhesives and additives;

[0037] The additive is a metal oxide having an inverse opal structure.

[0038] The negative electrode sheet provided in the embodiment of the present application has a metal oxide with an inverse opal structure added to the active layer of the negative electrode sheet. The metal oxide can give the negative electrode sheet a special pore structure, thereby increasing the porosity of the negative electrode sheet, increasing the wettability of the electrolyte to the negative electrode sheet, and increasing the liquid retention of the negative electrode sheet. Therefore, by adding a metal oxide with an inverse opal structure to the negative electrode active layer, the rate performance of the negative electrode sheet can be increased, the internal resistance of the battery cell can be reduced, and the transmission rate of lithium ions can be guaranteed at the same time. This negative electrode sheet can improve the problem of reduced electrolyte infiltration and reduced ion transmission rate caused by increasing the coating amount of the electrode sheet and the compaction density of the material to increase the energy density of the lithium-ion battery, thereby causing a decrease in rate performance and loss of battery power performance.

[0039] It should be noted that the preparation of metal oxides with inverse opal structures is currently a prior art, so it will not be described in detail in this case.

[0040] Optionally, the active layer can be disposed on any one side or two opposite sides of the current collector.

[0041] Optionally, in order to better improve the wettability and liquid retention properties of the negative electrode sheet, the active layer is a multi-layer structure; along the direction away from the current collector, the additive content of each layer in the multi-layer active layer gradually increases, and the additive is evenly distributed in each active layer.

[0042] Furthermore, in order to ensure that the negative electrode sheet has better high rate performance, the content of the additives in each layer of the multilayer structure of the active layer satisfies the following formula: The active layer closest to the current collector is the first layer, a1 is the percentage of the additive in the first layer to the entire active layer mass, a n is the percentage of the additive in the nth layer to the total active mass, n is the current layer number, n 总 is the total number of active layers, n 总 ≥2, p is the mass percentage of the additive in the entire active layer, 0.1%≤p≤50%;

[0043] When n 总≥2,0≤a1 <p / n 总 , a n Starting from the current collector side, it gradually increases to the outermost layer.

[0044] Preferably, the metal oxide is a metal oxide with lithium storage capacity. When the added metal oxide is a metal oxide with lithium storage capacity, it can ensure that the negative electrode has better lithium storage capacity and better energy density.

[0045] Optionally, to further ensure the electrochemical performance of the negative electrode sheet, the D50 of the metal oxide in the active layer is 1 to 40 μm. D50 within this range can not only improve the porosity of the negative electrode sheet, improve the wettability of the electrolyte to the negative electrode sheet, but also make the negative electrode sheet have a higher energy density. When D50 is less than 1 μm, the particle size is too small to improve the porosity of the negative electrode sheet. When D50 is greater than 40 μm, the compaction density of the negative electrode sheet will be reduced, thereby reducing the energy density of the lithium-ion battery. Preferably, D50 is 10 μm, 20 μm, or 30 μm.

[0046] Similarly, further, the internal pore size of the metal oxide particles is 0.05 to 20 μm. Within this range, not only the porosity of the negative electrode sheet can be improved, the wettability of the electrolyte to the negative electrode sheet can be improved, but also the negative electrode sheet can have a higher energy density. Preferably, the internal pore size is 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm. When the internal pore size of the metal oxide particles is less than 0.05 μm, the particle pore size is too small to effectively improve the porosity of the negative electrode sheet. When the internal pore size of the metal oxide particles is greater than 20 μm, the compaction density of the negative electrode sheet will be reduced, thereby reducing the energy density of the lithium-ion battery.

[0047] Similarly, further, the internal pore volume accounts for 50 to 90% of the particle volume. Within this range, not only the porosity of the negative electrode sheet can be improved, the wettability of the electrolyte to the negative electrode sheet can be improved, but also the negative electrode sheet can have a higher energy density. Preferably, the internal pore volume accounts for 60%, 70%, and 80% of the particle volume. When the internal pore volume accounts for less than 50% of the particle volume, the porosity of the negative electrode sheet cannot be effectively improved. When the internal pore volume accounts for more than 90% of the particle volume, the compaction density of the negative electrode sheet will be reduced, thereby reducing the energy density of the lithium-ion battery.

[0048] Optionally, the metal oxide is selected from at least one of titanium dioxide, tin dioxide and germanium dioxide.

[0049] Optionally, the active layer comprises, by mass percentage, 43-97.9% of negative electrode active material, 0.5-3% of conductive agent, 1-2.5% of binder and 0.1-50% of additive.

[0050] Optionally, to ensure that the negative electrode sheet has better performance, the coating surface density of the active layer is 40 to 400 g / m 2 .

[0051] Optionally, the negative electrode active material is selected from at least one of graphite, hard carbon, soft carbon, lithium titanate and mesophase carbon microspheres.

[0052] Optionally, the conductive agent is selected from at least one of carbon black, graphite flakes, carbon nanotubes and graphene.

[0053] Optionally, the adhesive is selected from at least one of styrene-butadiene rubber, sodium polyacrylate, sodium alginate and polyacrylonitrile.

[0054] Optionally, the active layer further comprises 0.5-1.5% of a dispersant in terms of mass percentage.

[0055] Optionally, the dispersant is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium carboxyethyl cellulose.

[0056] The method for preparing the negative electrode sheet provided in the embodiment of the present application is used to prepare the negative electrode sheet provided in the embodiment of the present application, comprising coating the negative electrode slurry containing various components of the active layer on the surface of the current collector, followed by drying and cold pressing.

[0057] Specifically, if the active layer is a single-layer structure, the negative electrode slurry is applied in one layer and then dried and cold pressed; if the active layer is a multi-layer structure, the negative electrode slurries corresponding to different layers are applied in sequence and then dried and cold pressed.

[0058] The lithium battery provided in the embodiment of the present application includes the negative electrode sheet provided in the embodiment of the present application. Since the battery includes the negative electrode sheet provided in the embodiment of the present application, it has better electrochemical performance.

[0059] The present application is further described below in conjunction with a number of embodiments and comparative examples.

[0060] Example 1

[0061] A negative electrode sheet, the preparation method of which is as follows:

[0062] Graphite, titanium dioxide with an inverse opal structure, conductive agent carbon black, adhesive styrene-butadiene rubber, and dispersant sodium carboxymethyl cellulose are mixed with water in a mass ratio of 47.5%:47.5%:2%:1.8%:1.2% to obtain a negative electrode slurry with a solid content of 45%. Among them, the titanium dioxide particle size D50 is 20μm, the internal pore size is 1-5μm, and the pore volume accounts for 70%.

[0063] The negative electrode slurry is coated on both sides of the current collector, dried, cold pressed and cut to obtain the negative electrode sheet, wherein the active layer coating surface density is 300g / m 2 .

[0064] Example 2

[0065] A composite negative electrode sheet, the preparation method is as follows:

[0066] Graphite, conductive agent carbon black, adhesive styrene-butadiene rubber, dispersant sodium carboxymethyl cellulose, and water are mixed in a mass ratio of 95%:2%:1.8%:1.2% to obtain a negative electrode slurry a with a solid content of 45%;

[0067] Titanium dioxide with an inverse opal structure, carbon black as a conductive agent, styrene-butadiene rubber as an adhesive, and sodium carboxymethyl cellulose as a dispersant are mixed with water in a mass ratio of 95%:2%:1.8%:1.2% to obtain a negative electrode slurry b with a solid content of 45%. Among them, the titanium dioxide particle size D50 is 20 μm, the internal pore size is 1 to 5 μm, and the pore volume accounts for 70%.

[0068] Slurry a is coated on both sides of the current collector, slurry b is coated on slurry a, dried, cold pressed and cut to obtain the negative electrode sheet, wherein the active layer coating surface density is 300g / m 2 , the first layer is 150g / m 2 , the second layer is 150g / m 2 .

[0069] The titanium dioxide with an inverse opal structure in the prepared negative electrode sheet is concentrated and dispersed on the side away from the current collector. The mass ratio of graphite, titanium dioxide, conductive agent, adhesive and dispersant in the negative electrode sheet is 47.5%:47.5%:2%:1.8%:1.2%.

[0070] The structure of the negative electrode sheet is as follows: Figure 1 As shown, a graphite layer 2 and an inverse opal porous layer 1 are sequentially formed on two opposite sides of a current collector 3 .

[0071] Example 3

[0072] A composite negative electrode sheet, the preparation method is as follows:

[0073] Graphite, conductive agent carbon black, adhesive styrene-butadiene rubber, dispersant sodium carboxymethyl cellulose and water are mixed in a mass ratio of 95%:2%:1.8%:1.2% to obtain a negative electrode slurry a with a solid content of 45%;

[0074] Graphite, titanium dioxide with an inverse opal structure, conductive agent carbon black, adhesive styrene-butadiene rubber, and dispersant sodium carboxymethyl cellulose were mixed with water in a mass ratio of 47.5%:47.5%:2%:1.8%:1.2% to obtain a negative electrode slurry b with a solid content of 45%. Among them, the titanium dioxide particle size D50 is 20 μm, the internal pore size is 1 to 5 μm, and the pore volume accounts for 70%.

[0075] Titanium dioxide with an inverse opal structure, carbon black as a conductive agent, styrene-butadiene rubber as an adhesive, sodium carboxymethyl cellulose as a dispersant, and water are mixed in a mass ratio of 95%:2%:1.8%:1.2% to obtain a negative electrode slurry C with a solid content of 45%. Among them, the titanium dioxide particle size is 20 μm, the internal pore size is 1 to 5 μm, and the pore volume accounts for 70%.

[0076] According to the arrangement of each layer of the active layer, the formula is satisfied. n 总 =3, a1=0, p=47.5%; that is, the additive content of the first layer of the active layer is 0, the content of the second layer is 15.83%, and the content of the third layer is 31.67%. Slurry a is coated on both sides of the current collector, slurry b is coated on slurry a, and slurry c is coated on slurry b, dried, cold pressed, and cut to obtain the negative electrode sheet, wherein the active layer coating surface density is 300g / m 2 , the first layer is 100g / m 2 , the second layer is 100g / m 2 , the third layer is 100g / m 2 .

[0077] In the prepared negative electrode sheet, titanium dioxide with an inverse opal structure is gradiently dispersed on the side away from the current collector, and the mass ratio of graphite, titanium dioxide, conductive agent, adhesive and dispersant in the negative electrode sheet is 47.5%:47.5%:2%:1.8%:1.2%.

[0078] The structure of the negative electrode sheet is as follows: Figure 2 As shown, a graphite layer 2 and an inverse opal and graphite mixed porous layer 4 are sequentially formed on opposite sides of a current collector 3 .

[0079] Example 4

[0080] This embodiment is basically the same as Embodiment 3, except that: this embodiment does not satisfy the formula The additive content of the first layer is 15.83%, the content of the second layer is 31.67%, and the content of the third layer is 0%.

[0081] Slurries a, b and c were prepared in the same manner as in Example 3. Slurry b was coated on both sides of the current collector, slurry c was coated on slurry b, and slurry a was coated on slurry c. The mixture was dried, cold pressed and cut to obtain negative electrode sheets.

[0082] The titanium dioxide with an inverse opal structure in the prepared negative electrode sheet is not distributed according to the formula. The mass ratio of graphite, titanium dioxide, conductive agent, adhesive and dispersant in the negative electrode sheet is 47.5:47.5%:2%:1.8%:1.2%.

[0083] Example 5

[0084] This embodiment is basically the same as Embodiment 2, except that the coating order of slurry a and slurry b is exchanged.

[0085] Example 6

[0086] This embodiment is basically the same as embodiment 2, except that the components of slurry a are graphite: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose = 95%: 2%: 1.8%: 1.2%;

[0087] The components of slurry b are graphite: titanium dioxide with an opal structure: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose in a mass ratio of 94.8%: 0.2%: 2%: 1.8%: 1.2%.

[0088] The titanium dioxide with an inverse opal structure in the prepared negative electrode sheet is concentrated and dispersed on the side away from the current collector. The mass ratio of graphite, titanium dioxide, conductive agent, adhesive and dispersant in the negative electrode sheet is: 94.9%: 0.1%: 2%: 1.8%: 1.2%, of which the additive content in the first layer is 0% and the content in the second layer is 0.1%.

[0089] Similarly, the active layer coating surface density is 300g / m 2 , the first layer is 150g / m 2 , the second layer is 150g / m 2 .

[0090] Example 7

[0091] This embodiment is basically the same as embodiment 2, except that the components of slurry a are graphite: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose = 95%: 2%: 1.8%: 1.2%;

[0092] The components of slurry b are graphite: titanium dioxide with an opal structure: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose in a mass ratio of 75%: 20%: 2%: 1.8%: 1.2%.

[0093] The titanium dioxide with an inverse opal structure in the prepared negative electrode sheet is concentrated and dispersed on the side away from the current collector, and the mass ratio of graphite, titanium dioxide, conductive agent, adhesive, and dispersant in the negative electrode sheet is: 85%: 10%: 2%: 1.8%: 1.2%. The content of the additive in the first layer is 0%, and the content in the second layer is 10%.

[0094] Similarly, the active layer coating surface density is 300g / m 2 , the first layer is 150g / m 2 , the second layer is 150g / m 2 .

[0095] Example 8

[0096] This embodiment is basically the same as embodiment 2, except that the components of slurry a are graphite: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose = 95%: 2%: 1.8%: 1.2%;

[0097] The components of slurry b are graphite: titanium dioxide with an opal structure: conductive agent carbon black: adhesive styrene-butadiene rubber: dispersant sodium carboxymethyl cellulose in a mass ratio of 55%: 40%: 2%: 1.8%: 1.2%.

[0098] The titanium dioxide with an inverse opal structure in the prepared negative electrode sheet is concentrated and dispersed on the side away from the current collector, and the mass ratio of graphite, titanium dioxide, conductive agent, adhesive, and dispersant in the negative electrode sheet is: 75%: 20%: 2%: 1.8%: 1.2%. The content of the additive in the first layer is 0%, and the content in the second layer is 20%.

[0099] Similarly, the active layer coating surface density is 300g / m 2 , the first layer is 150g / m 2 , the second layer is 150g / m 2 .

[0100] Comparative Example

[0101] A negative electrode sheet, the preparation method is as follows:

[0102] Graphite, conductive agent carbon black, adhesive styrene-butadiene rubber, dispersant sodium carboxymethyl cellulose and water are mixed to obtain a negative electrode slurry with a solid content of 45%, which is coated on both sides of the current collector, dried, cold pressed and cut to obtain a negative electrode sheet.

[0103] Experimental example

[0104] The negative electrode plates of each embodiment and comparative example are assembled into a soft-pack lithium-ion battery, wherein the positive electrode plates, separators and electrolytes involved are specifically as follows:

[0105] Preparation of positive electrode sheets: lithium iron phosphate, conductive agent, adhesive are mixed with N-methylpyrrolidone in a mass ratio of 95.5%:2.5%:2% to obtain a positive electrode slurry with a solid content of 55%, which is coated on both sides of an aluminum foil current collector, dried, cold pressed, and cut to obtain positive electrode sheets.

[0106] Diaphragm: Polypropylene diaphragm with a thickness of 16μm.

[0107] Preparation of electrolyte: dimethyl carbonate, ethylene carbonate and diethyl carbonate were mixed at a ratio of 1:1:1, and lithium hexafluorophosphate was added, wherein the concentration of lithium hexafluorophosphate was 1.1 mol / L.

[0108] (1) Pole piece porosity test: Cut the pole piece to a certain size, calculate the apparent volume V1, use a true density tester to test and get the real volume V2 of the pole piece, and then calculate the porosity according to (V1-V2) / V1×100%.

[0109] (2) Rate discharge performance test: charge at 1C constant current and constant voltage to 3.65V at 25℃, cut off the current at 0.05C, leave for 30min, discharge at nC constant current to 2.2V, record the discharge capacity retention rate, n=1, 3, 5, the discharge capacity retention rate is nC discharge capacity / 1C discharge capacity×100%.

[0110] (3) DC internal resistance DCR test: adjust to 50% SOC state at 25°C, leave for 1 hour, record OCV1, discharge at 3C for 10 seconds, record OCV2, and then calculate DCR according to (OCV1-OCV2) / 3C×1000. Record the test results in Table 1.

[0111] Table 1 Test results of various embodiments and comparative examples

[0112]

[0113] It can be seen from the test data in Table 1 that the negative electrode sheets prepared in various embodiments of the present application have better performance after being assembled into batteries.

[0114] Comparing Examples 1 to 3 with the comparative example, the additive content is high, the porosity is significantly higher, the capacity retention rate is significantly higher, and the DC internal resistance is significantly smaller.

[0115] Comparing Example 5 with Example 2, Example 2 has better performance. Comparing Example 1 with Example 2, Example 2 has better performance, which indicates that when the titanium dioxide with an inverse opal structure is concentrated on the outer side of the negative electrode sheet, it has better electrochemical performance.

[0116] Comparing Example 2 with Example 6, Example 7, and Example 8, Example 2 has better electrochemical performance, which means that when titanium dioxide is distributed on the outside, the higher the content, the better the rate performance and the smaller the DC internal resistance.

[0117] Comparing Example 4 with Example 3, Example 3 has better performance, which means that the content is higher toward the outside and the electrochemical performance is better when the requirements of the formula provided in this application are met.

[0118] In summary, the negative electrode sheet provided in the embodiment of the present application has a metal oxide with an inverse opal structure added to the active layer of the negative electrode sheet, which can give the negative electrode sheet a special pore structure, improve the porosity of the negative electrode sheet, improve the wettability of the electrolyte to the negative electrode sheet, and improve the liquid retention of the negative electrode sheet. The metal oxide selected as an additive with a lithium storage function will not reduce the lithium storage capacity of the negative electrode. Therefore, by adding a metal oxide with a lithium storage function with an inverse opal structure to the negative electrode active layer, the energy density and rate performance of the negative electrode sheet can be increased, and the transmission rate of lithium ions can also be guaranteed. This negative electrode sheet can improve the problem of reduced electrolyte infiltration and reduced ion transmission rate when the energy density of lithium-ion batteries is increased by increasing the coating amount of the electrode sheet and the compaction density of the material, thereby causing a decrease in rate performance and loss of battery power performance.

[0119] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A negative electrode sheet, characterized in that: It includes a current collector and an active layer arranged on the surface of the current collector; The active layer comprises negative electrode active materials, conductive agents, adhesives and additives; The additive is a metal oxide having an inverse opal structure.

2. The negative electrode sheet according to claim 1, characterized in that: The active layer is a multi-layer structure; Along the direction away from the current collector, the content of the additive in each layer of the active layer of the multi-layer structure gradually increases.

3. The negative electrode sheet according to claim 2, characterized in that: The content of the additive in each layer of the multilayer structure of the active layer satisfies the following formula: The active layer closest to the current collector is the first layer, a1 is the percentage of the additive in the first layer to the mass of the entire active layer, and a n is the percentage of the additive in the nth layer to the total active mass, n is the current layer number, n 总 is the total number of active layers, n 总 ≥2, p is the mass percentage of the additive in the entire active layer, 0.1%≤p≤50%; When n_total ≥ 2, 0 ≤ a1 < p / n_total, a n Starting from the current collector side, it gradually increases to the outermost layer.

4. The negative electrode sheet according to claim 1, characterized in that: The metal oxide satisfies: The D50 of the metal oxide is 1 to 40 μm; and / or, The internal pore size of the metal oxide particles is 0.05-20 μm, and the internal pore volume accounts for 50-90% of the particle volume.

5. The negative electrode sheet according to claim 4, characterized in that: The metal oxide is selected from at least one of titanium dioxide, tin dioxide and germanium dioxide.

6. The negative electrode sheet according to any one of claims 1 to 5, characterized in that: The active layer comprises, by mass percentage, 43-97.9% of the negative electrode active material, 0.5-3% of the conductive agent, 1-2.5% of the binder and 0.1-50% of the additive.

7. The negative electrode sheet according to claim 6, characterized in that: The active layer also includes 0.5 to 1.5% of a dispersant by mass percentage; The dispersant is selected from at least one of sodium carboxymethyl cellulose, lithium carboxymethyl cellulose and sodium carboxyethyl cellulose.

8. The negative electrode sheet according to claim 1, characterized in that: Also includes at least one of the following features (1)-(4): (1) The conductive agent is selected from at least one of carbon black, graphite flakes, carbon nanotubes and graphene; (2) The adhesive is selected from at least one of styrene-butadiene rubber, sodium polyacrylate, sodium alginate and polyacrylonitrile; (3) The negative electrode active material is selected from at least one of graphite, hard carbon, soft carbon, lithium titanate and mesophase carbon microspheres; (4) The active layer is disposed on two opposite sides of the current collector.

9. A method for preparing a negative electrode sheet, characterized in that: The method for preparing the negative electrode sheet according to any one of claims 1 to 8 comprises coating a negative electrode slurry containing various components of the active layer on the surface of the current collector, followed by drying and cold pressing.

10. A lithium battery, characterized in that: The invention comprises the negative electrode sheet as claimed in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Method for preparing primary battery of inverse opal polypyrrole anode material

    CN102340010A

  • Negative pole piece and lithium ion battery

    CN114079048A

  • Lithium metal negative electrode with protective film capable of regulating and controlling lithium ion deposition process and preparation method of lithium metal negative electrode

    CN117638004A

  • Negative plate and preparation method thereof, battery cell and battery

    CN118117035A

  • Negative pole piece and preparation method thereof, battery and power utilization device

    CN118335980A

Cited By

  • Negative electrode sheet and preparation method therefor, and lithium battery

    WO2026091671A1